MANAJEMEN PEMASARAN HASIL PRODUK AGROFORESTRY DI DESA TIBO KECAMATAN SINDUE TOMBUSABORAKABUPATEN DONGGALA - Awalia, Lulu; Umar, Syukur; Alam, Andi Sahri (Jurnal Warta Rimba, 2019)
Agroforestry has been known to have a very important role in helping to reduce poverty in rural areas. Firewood, fruits, nuts, medicinal plants, raw materials for crafts such as rattan and bamboo, and various other agroforestry products are collected by small farmers and sold in traditional markets. The income derived from these agroforestry products is usually used as a safety net for poor farming families, agroforestry is generally practiced on a relatively limited plot of land (on average less than one hectare) due to the widely supported community land ownership. The purpose of this study was to determine the marketing channel of agroforestry products and analyze the marketing margins and marketing efficiency results of agroforestry products in the village of Tibo Tombusabora, Sindue District, Donggala Regency. The location of this research was carried out in the village of Tibo Tombusabora, Donggala Regency. The sample used in this study was purposive sampling technique. Based on the results of research conducted obtained analysis of the total marketing margins of cocoa, rambutan and chili in the village of Tibo are the same, both between the first channel and the second channel are cocoa Rp3.61%, rambutan Rp6.97% and chili Rp. 3.22 % with the existing efficiency level for each channel, where the first level efficiency channel is Cocoa 5.08%, Rambutan 8.14% and Chili 4.19% and the second level efficiency channel namely Cocoa 7.60%, Rambutan 1.21 % and 6.28% Chili.Keywords: Marketing Management, Agroforestry, Tibo Village.